2021
DOI: 10.1021/jacs.1c05386
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation of a Human Microprotein Promotes Dissociation of Biomolecular Condensates

Abstract: Proteogenomic identification of translated small open reading frames in humans has revealed thousands of microproteins, or polypeptides of fewer than 100 amino acids, that were previously invisible to geneticists. Hundreds of microproteins have been shown to be essential for cell growth and proliferation, and many regulate macromolecular complexes. However, the vast majority of microproteins remain functionally uncharacterized, and many lack secondary structure and exhibit limited evolutionary conservation. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…mRNA decapping proteins are responsible for promoting 5′-3′ decay via removing the 5′ cap from mRNAs and participating in the turnover of mRNA and nonsense-mediated decay. Endogenous NBDY regulates cellular RNA decapping by directly interacting with the decapping proteins via EDC4 and DCP1A proteins and localizing to P-bodies. , In addition, in vitro, in the presence of RNA, NBDY undergoes liquid–liquid phase separation . NBDY phosphorylation promotes liquid phase remixing in vitro and macroscopic P-body segregation in cells that undergo growth factor signaling and cell division .…”
Section: Micropeptides Encoded By Lncrna-derived Sorfsmentioning
confidence: 99%
See 2 more Smart Citations
“…mRNA decapping proteins are responsible for promoting 5′-3′ decay via removing the 5′ cap from mRNAs and participating in the turnover of mRNA and nonsense-mediated decay. Endogenous NBDY regulates cellular RNA decapping by directly interacting with the decapping proteins via EDC4 and DCP1A proteins and localizing to P-bodies. , In addition, in vitro, in the presence of RNA, NBDY undergoes liquid–liquid phase separation . NBDY phosphorylation promotes liquid phase remixing in vitro and macroscopic P-body segregation in cells that undergo growth factor signaling and cell division .…”
Section: Micropeptides Encoded By Lncrna-derived Sorfsmentioning
confidence: 99%
“…Endogenous NBDY regulates cellular RNA decapping by directly interacting with the decapping proteins via EDC4 and DCP1A proteins and localizing to P-bodies. , In addition, in vitro, in the presence of RNA, NBDY undergoes liquid–liquid phase separation . NBDY phosphorylation promotes liquid phase remixing in vitro and macroscopic P-body segregation in cells that undergo growth factor signaling and cell division . Moreover, STORM, a linc00689-derived micropeptide, induced by TNF-α-induced and MST1-mediated eIF4E phosphorylation of eIF4E, exhibits molecular mimicry of SRP19 and thus competes for 7SL RNA …”
Section: Micropeptides Encoded By Lncrna-derived Sorfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation can confer unique properties to organic compounds (proteins, amino acids, sugars, and hydroxyl compounds), such as chemical stability, biodegradability, emulsion dispersion, and antistatic properties. Both chemical and biocatalytic methods have been developed for the phosphorylation reaction. Biocatalytic methods are widely used based on their advantages of high regioselectivity and environmentally friendly processes. However, biocatalytic phosphorylation has been achieved mainly using kinases, which has limited their application due to the requirement for expensive high-energy phosphate donors (ATP) and narrow substrate spectrum. By contrast, acid phosphatases (APases; EC 3.1.3.2) can catalyze the phosphorylation reaction using cheap phosphate donors, e.g., pyrophosphate (PPi) or polyphosphates and having a broad substrate spectrum that includes unnatural substrates. For example, the synthesis of 5′-inosine monophosphate (5-IMP) via APase-catalyzed inosine phosphorylation is a representative case at an industrial scale .…”
Section: Introductionmentioning
confidence: 99%
“…Aguilera-Gomez et al [140] highlighted the general importance of MARylation in the formation and control of condensates in the Drosophila oocyte. Similarly, phosphorylation of NBDY (which is an intrinsically disordered protein) has been shown by Na et al [141] to be linked with the stability of P-bodies. Similarly, Saurabh et al [142] showed in vivo that ATP depletion promotes phase separation in eukaryotic cells, also see Ref.…”
Section: Continuous Model Of Passive Phase Separation With Chemical R...mentioning
confidence: 78%